Toxicological Analysis of Some Drugs of Abuse in Biological Samples - Anne Marie Ciobanu; Daniela Baconi; Cristian Bălălău; Carolina Negrei; Miriana Stan; Maria Bârcă (Journal of Mind and Medical Sciences)
Consumption of drugs of abuse is a scourge of modern world. Abuse, drug addiction and their consequences are one of the major current problems of European society because of the significant repercussions in individual, family, social and economic level. In this context, toxicological analysis of the drugs of abuse in biological samples is a useful tool for: diagnosis of drug addiction, checking an auto-response, mandatory screening in some treatment programs, identification of a substance in the case of an overdose, determining compliance of the treatment. The present paper aims to address the needs of healthcare professionals involved in drugs addiction treatment through systematic presentation of information regarding their toxicological analysis. Basically, it is a tool that help you to select the suitable biological sample and the right collecting time, as well as the proper analysis technique, depending on the purpose of analysis, pharmacokinetic characteristics of the drugs of abuse, available equipment and staff expertise.